HSCT-GAVE as a Manifestation of Chronic Graft versus Host Disease: A Case Report and Review of the Existing Literature. (12th March 2018) - Grant, Michael J.; Horwitz, Mitchell E.
Abstract : Gastric antral vascular ectasia or "watermelon stomach" is a significant cause of nonvariceal upper GI bleeding and is characterized by red, tortuous ectatic vessels along longitudinal folds in the gastric antrum. The existing literature links GAVE to patients with cirrhosis, scleroderma, bone marrow transplantation, and chronic renal failure among other associations, but its pathophysiology remains ill-defined. Over 30 cases of hematopoietic stem cell transplant-related GAVE (HSCT-GAVE) have been reported in the literature to date and there are likely many more that go undiagnosed or are attributed to another cause of upper gastrointestinal bleeding. Interestingly, a busulfan-containing conditioning regimen has been the primary factor implicated in the etiology of HSCT-GAVE because this was common to all cases in the literature to date. Here, we present the first case of HSCT-GAVE in a patient that was treated with a non-busulfan-containing conditioning regimen. We propose a link between chronic GVHD and the development of HSCT-GAVE that is supported by a similar development of GAVE in patients with systemic sclerosis.